Apelin and APLN single nucleotide polymorphisms and combined hypertension and central retinal artery stenosis in a Chinese population. (July 2015) - Zhu, Pengli; Lin, Fan; Huang, Feng; Huang, Qiuxia; Li, Qiaowei; Gao, Zhonghai; Chen, Falin
Abstract Apelin activity plays a role in regulating blood pressure. This study explored the relationship between single nucleotide polymorphisms (SNPs) in the Apelin gene (APLN) with hypertension and hypertension with central retinal artery equivalent (CRAE) stenosis in a coastal Chinese population. All subjects answered an epidemiological survey for demographic and disease characteristics. Apelin levels were determined and three APLN SNPs, rs56204867, rs3115757, and rs3761581, were evaluated. CRAE was measured using fundus photography. Apelin levels were significantly lower in subjects with hypertension and hypertension with CRAE stenosis (0.23 ± 0.10 ng/ml and 0.21 ± 0.08 ng/ml, respectively) compared with control subjects (0.25 ± 0.11 ng/ml; p < 0.001). Linear regression analysis showed hypertension and hypertension with CRAE stenosis was associated with age, being male, systolic blood pressure, abnormal blood lipids, and Apelin levels. Genetic analysis indicated that in both males and females SNP rs3761581 was associated with hypertension and that more males carrying rs56204867 and rs3761581 T-A haplotype had hypertension (61.88%) and hypertension with CRAE stenosis (56.82%) than control males (39.33%). In this Chinese population, Apelin and APLN SNP rs3761581 was associated with combined hypertension with CRAE, indicating that the expression of APLN gene products may be involved in vascular injury.